Identification of drought-tolerant spring wheat genotypes - Henrique Caletti Mezzomo; Caique Machado e Silva; João Paulo Oliveira Ribeiro; Davi Soares de Freitas; Aluizio Borém; Maicon Nardino (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to use drought-tolerance indices to classify spring wheat genotypes regarding their tolerance to drought environments, as well as to evaluate their genetic diversity for the selection of potential parents with this trait. Thirty-six wheat genotypes were evaluated in 2020, under two treatments in the field: one with irrigation (control) and the other with water stress. Grain yield was determined, and the obtained results were used to build five different drought-tolerance indices. The data were subjected to the mixed model analysis to estimate genetic parameters and predict genotypic values. The genotypic values of the studied variables were subjected to the genetic diversity analysis using the unweighted pair group method with arithmetic mean and to the principal component analysis. The random genotypic effect was significant for all studied traits. Genotypes VI 131313, VI 14001, VI 14055, VI 14118, VI 14197, VI 14214, VI 14239, VI 9004, and 'BRS 264' can be grown under drought-stress conditions. The used indices are useful to classify the genotypes in terms of drought-tolerance. Therefore, the proposed methodology allows of investigating genetic diversity and selecting genotypes based on their tolerance to drought.